Implementação de política pública de segurança: Programa Pacto Pela Vida na Bahia - SANTANA, Maribel Fernandes Ribeiro Santana (2016)
This work aims to analyze the conditions of implementation factors Security Public Policy in the State of Bahia called Pact Program for Life, with a model of cross-government management, focused on integrated operations, reducing violence and citizen security model. The work seeks to describe the factors that influenced the implementation process of this public policy, the model of management between the involved departments, through the Sectoral Chambers, highlighting aspects institutional, organizational and operational. Based on the analysis of the cycle described by SECCHI (2010), the seven phases of public policies will be addressed: problem identification, agenda formation, formulation of alternatives, decision making, implementation, evaluation and closure, emphasizing the implementation of the policy. Based on SABATIER (1986), the synthesis of models for implementation was used: top-down and bottom-up. In this study, we surveyed the departments involved in the Pact for Life and thematic sectoral chambers and analyzed the main findings inherent in the process of formulation and implementation of the program. In the survey, a qualitative approach was used as a research strategy the case study method, and the methodological procedures used were questionnaires, exploratory interviews and finally the content analysis. Official statistics of the Security of the Secretariat pointed out that the Bahia, with the implementation of the Pact for Life program, which the analysis period the PPA 2012-2015, showed significant results in reducing the number of homicides, and with this program, the State consolidated a government management model that seeks efficiency and scope of indicators to improve public safety and social prevention.